Penggunaan ragi roti (Saccharomyces cerevisiae) sebagai imunostimulan untuk meningkatkan resistensi ikan mas (Cyprinus carpio L) terhadap infeksi bakteri Aeromonas hydrophila - Manoppo, Henky; Kolopita, Magdalena E.F. (Universitas Sam Ratulangi, 2016)
A research had been conducted to evaluate the use of baker’s yeast as immunostimulant in enhancing the resistance of carp (Cyprinus carpio L) to Aeromonas hydrophila infection. Experimental fish were obtained from Freshwater Aquaculture Board in Talelu, Minahasa Regency, and transported to the Laboratory of Aquaculture Technology at the Faculty of Fisheries and Marine Science, Sam Ratulangi University. During two weeks of acclimatization process, fingerlings were fed with commercial feed (pellet) at 5% of body weight per day, twice a day. After acclimatization, fish was randomly distributed into 15 aquaria with a density of 25 fishes/aquarium. The doses of yeast cells as treatments included 5, 10, 15 and 20 g yeast/kg of pellet while control pellet not supplemented with yeast cell. Fish was fed with treatment pellets for four consecutive weeks at 5% of body weight per day, twice daily at 09.00 am and 16.00 pm. Afterward, the density of fish were adjusted to 10 fish/aquarium. Fish were then challenged with A. hydrophila through intraperitoneal injection of 0.2 mL of A. hydrophila suspension containing 1x107 cfu/mL. Research result showed that supplementation of yeast cells into fish pellet significantly influenced the resistance of fish to A. hydrophila infection (p<0,01). The highest resistance were observed in fish fed pellet supplemented with 5 g yeast/kg of pellet. Thus, supplementation of baker’s yeast cells into commercial fish feed was able to increase resistance of carp to A. hydrophila infection. Keywords: baker’s yeast, Cyprinus carpio, A. hydrophila, resistance, intraperitoneal injection